Особливості формування структури нанокомпозитів дигліцидилового етеру дифенілолпропану та глюкози - Віленський, В.О.; Овсянкіна, В.О.; Гончаренко, Л.А.; Менжерес, Г.Я. (Видавничий дім "Академперіодика" НАН України, 2007)
We have first studied the peculiarities of the structure of nanocomposites on the basis of epoxy resin and monohydrate D-glucose. It is shown that the narrow temperature interval for these compounds to coexist in a composite and the possibility to form an infinite crystalline cluster in the composition of polyepoxy impose the limitations on the structure of a nanocomposite and its chemical construction.